Pulmonary Tumor Thrombotic Microangiopathy - Ali, Hyeon-Ju; Cui, Shengjie; Sahay, Sandeep; Grosu, Horiana B.; Riben, Michael W.; Deswal, Anita; Mouhayar, Elie; Iliescu, Cezar; Ali, Abdelrahman; Faiz, Saadia A. (JACC. Case reports, 2025)
Pulmonary hypertension in patients with advanced solid organ tumors may be secondary to a rare diagnosis of pulmonary tumor thrombotic microangiopathy. Current literature is limited to case reports, and there is no consensus on diagnosis and management. This case highlights the importance of a high degree of clinical suspicion and the role of additional work-up for pulmonary tumor thrombotic microangiopathy including fludeoxyglucose-19–positron emission tomography and cytology of pulmonary artery blood sample at the time of right-sided heart catheterization. Future studies are needed to better understand the role of pulmonary vasodilators and targeted therapies, such as platelet-derived growth factor inhibitors, and their impact on the clinical outcomes for patients with poor prognosis secondary to their cancers. [Display omitted]